Teacher perspectives on pedagogical changes : an ethnographic study in the rural primary schools of Tamil Nadu, India - Soundararaj, Gomathy (2019)
The study seeks to understand and analyse the pedagogical changes and its implementation process in Tamil Nadu, India. It aims to understand the perspectives of the rural government teachers when the state introduces pedagogical changes based on constructivism such as the Simplified Activity Based Learning (SABL) in the schools. The study captures the transition process, focusing on aspects of the pedagogical change such as the role of a teacher, use of digital technology and the teacher professional development program from the standpoint of the teachers. The findings of the study reveal that the teachers struggle to define their role in a child centered pedagogy classroom with obstacles in terms of their ideologies, society and support in implementation. With digital technology based instruction, teachers faced major hindrances in the form of their beliefs, lack of resources and problems with the in-service teacher training program. While the in-service teacher training conveys content and information it fails to address the needs of the teachers and enhance teacher agency. The teachers expressed a disconnect with their facilitators and pointed out the absence of demonstration classes, discussion and collaboration along with the issues in time allocation and consistency. With such findings, the study proposes recommendations to address and integrate teacher agency, teacher interaction and collaboration to make it more impactful. It includes creating an egalitarian space with changing lecture-based sessions to design thinking and appreciative inquiry processes that connects the facilitators and teachers, enables a better understanding of the pedagogy and empowers teachers to be the agents of change.